Essential endodontology : prevention and treatment of apical periodontitis - Ørstavik, Dag (Wiley-Blackwell, 2020)
The 3rd edition explores the scientific basis of endodontology, adopting a systematic analysis of the available clinical and laboratory evidence. It focuses on the biology and clinical features of apical periodontitis, its diagnosis, prevention and treatment. Resource for practicing endodontists, postgraduate students of endodontology and those seeking professional certification in endodontology.
Keywords: periapikální periodontitida; Endodontics; zubní lékařství; Periapical Periodontitis; endodoncie